An experience of management of cluster endophthalmitis in western hilly rural region of Nepal: A descriptive, interventional study - Bastola, P (Journal of Chitwan Medical College, 2017)
Infectious endophthalmitis is among the most serious complications of cataract surgery. Cluster endophthalmitis is defined as five or more cases of endophthalmitis occurring on a particular day in a single operating room in one centre. The study aimed to find out causative organisms, ocular status and visual outcome after an outbreak of cluster endophthalmitis in a high volume cataract surgery in a camp. A descriptive, interventional study was carried out in 18 suspected cases of acute endophthalmitis after manual small incision cataract surgery in a single day. All clinically suspected cases underwent vitreous tap and received intravitreal injections. Vitreous samples were sent for staining and KOH mount, culture, sub-culture and sensitivity test was carried out in all vitreous specimens. Standard treatment protocol was followed. Patients were followed up till six weeks. Of the 89 eyes operated, 18 (20.2%) eyes underwent vitreous tap and intravitreal injections. Mean duration of presentation was 36 hours (24 – 48 hours). Commonest presenting symptom was redness 18 (100%), pain 83.3% (15) followed by decreased vision 77.8% (14). 10 (55.6%) eyes were culture negatives while, 8 (44.4%) were culture positive for pseudomonas aeruginosa. Six (33.3%) eyes needed core vitrectomy and repeat intravitreal injections, whereas 2 (11.1%) eyes needed repeat intravitreal injections only. Eight eyes (44.4%) got a normal visual acuity; two eyes (11.1%) fair and 8 eyes (44.4%) had poor visual acuity according to World Health Organisation (WHO) guidelines. Four eyes (22.2%) needed evisceration, while three (16.7%) eyes progressed to phthisis bulbi. Acute post operative endophthalmitis is a serious complication following cataract surgery. Prognosis of cluster endophthalmitis with proven culture positivity to pseudomonas infection is poor even with prompt standard management.